ANALISA LAJU KOROSI PADA SAMBUNGAN ELBOW PIPA MINYAK DI PT. PLN ( PERSERO ) ULPLTD POKA - Suparman, Widianti; Pelasula, Berthy; Patty, Alexander A. (Jurusan Teknik Mesin, 2024)
The oil pipeline network is a critical infrastructure that plays a vital role in the oil and gas industry. However, one of the significant challenges faced by this pipeline system is corrosion. Corrosion is a chemical process that leads to the deterioration of metal quality due to electrochemical reactions with the environment. Corrosion in oil pipelines not only reduces the wall thickness but can also result in leaks, structural damage, and even accidents that negatively impact human safety and the environment.The objective of this research is to analyze the corrosion rate in the elbow joints of oil pipelines at PT PLN (Persero) ULPTD Poka. This study employs a quantitative method involving two variables. The independent variable is the elbow type, specifically the 90Â° elbow, while the dependent variables are the corrosion rate calculations and the remaining service life (RSL) of the elbow pipes.The results indicate that the corrosion rate varies at each measurement point on the elbow joints. The RSL calculations show significant variation based on the thickness of the pipe wall at each elbow. The highest RSL values were found in elbows 3, 4, 5, and 8, with a remaining service life of up to 49.5 years. Conversely, elbow 1 had the lowest RSL at 38 years. The higher RSL in some elbows suggests that despite experiencing corrosion, the remaining thickness is still sufficient to support the pipeline's function for a longer duration. Recommendations include the need for intensive maintenance on the oil pipeline elbow joints, especially on segments above ground and near corrosive sources. Keywords: Oil Pipeline, Corrosion Elbow Joint, Remaining Service Life (RSL), Maintenance